Analysis of Differential Components in Green Teas from Five Huangjincha Cultivars Using Ultra-high Performance Liquid Chromatography-Quadrupole Orbitrap Mass Spectrometry - XIANG Bowen, ZHAO Yang, QU Furong, YANG Peidi, WANG Runlong, TU Hongqiang, LIU Zhen (Shipin Kexue)
To explore differential metabolites among green teas made from different Huangjincha cultivars, this study combined sensory evaluation, high performance liquid chromatography (HPLC), and ultra-high performance liquid chromatography-quadrupole orbitrap mass spectrometry (UPLC-Q-Exactive/MS)-based metabolomics to compare the quality and biochemical components of five Huangjincha green teas (Baojing Huangjincha 1, Huangjincha 2, Huangjincha 3, Huangjincha 5, and Huangjincha 16). The sensory evaluation results indicated that each Huangjincha green tea had its own characteristics. A total of 173 metabolites were identified and classified into 11 categories including 16 N-ethyl-2-pyrrolidinone-substituted flavan-3-ol (EPSF) compounds. The contents of 16 metabolites quantitatively determined by HPLC were consistent with the metabolomics results. Huangjincha 5, Huangjincha 3, and Huangjincha 16 were grouped into one cluster, while Baojing Huangjincha 1 and Huangjincha 2 were grouped into another. Baojing Huangjincha 1 had relatively high contents of amino acids and theanine, as well as the total amount of 9 EPSF compounds. The contents of procyanidins, isovitexin, luteolin-8-C-glucoside, and vitexin in Huangjincha 2 was relatively high. Huangjincha 3 had high contents of water extract, tea polyphenols, epigallocatechin-3-O-(3-O-methyl)-gallate (EGCG3’’Me), epigallocatechin-3-O-(4-O-methyl)gallate (EGCG4’’Me). Huangjincha 5 had high contents of apigenin, orientin, kaempferol, and theaflavins. Benzyl primeveroside as an aroma precursor was found to be the differential metabolite in Huangjincha 2 and Huangjincha 16 versus Baojing Huangjincha 1, with the highest up-regulation fold change being observed for both Huangjincha 2 and Huangjincha 16. Furthermore, 13, 10, 9, 17, and 5 shared differential metabolites were identified in Baojing Huangjincha 1, Huangjincha 2, Huangjincha 3, Huangjincha 5, and Huangjincha 16 versus four other cultivars, respectively. This study will provide a reference for the breeding and identification of Huangjincha green tea.